The Role of Business Communication in Improving Sales in The Food and Beverage Industry (Case Study on Gozadera Bar De Tapas) - Sri Mita Fitriani; Titis Tatasari (INCOME: Innovation of Economics and Management, 2023)
The food and beverage sector has been around for a while and has produced goods. A business classification encompassing the food and beverage industry is any enterprise that centers its operations around food or beverages, including F&B services. Maintaining a high standard of continuity and excellence in business communication is essential since customer or colleague satisfaction is critical to corporate success. Thus, this study aims to examine the role that business communication plays in increasing sales in the food and beverage industry and the challenges associated with business communication. Using a descriptive-analytical approach methodology, the research technique applies qualitative research focusing on business communication. In particular, Gozadera Bar De Tapas, one of the F&B Industry companies, is the target of this investigation. Primary data was the source of the information, and focus group discussions, observations, and interviews with relevant parties served as information collection techniques. Additionally, this study's information strategy involves analyzing qualitative data that field analysts have gathered. The findings indicate that effective corporate communication—including that with coworkers, leaders, and employees—and with customers and business partners- all significantly impact boosting sales. Through social media, business communications are conducted both directly and indirectly. Communication barriers can include misinterpretations of what is being said, loud music that interferes with normal hearing, and disagreements.